2016
DOI: 10.1007/s00330-016-4328-0
|View full text |Cite
|
Sign up to set email alerts
|

Grading diffuse gliomas without intense contrast enhancement by amide proton transfer MR imaging: comparisons with diffusion- and perfusion-weighted imaging

Abstract: • Amide proton transfer (APT) imaging helps in grading non-enhancing gliomas • High-grade gliomas showed higher APT signal than low-grade gliomas • APT imaging showed better diagnostic performance than diffusion- and perfusion-weighted imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
69
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(73 citation statements)
references
References 22 publications
4
69
0
Order By: Relevance
“…This study confirmed that APT imaging can be used for grading glial tumors, with a diagnostic accuracy comparable with that of other imaging biomarkers derived from DWI and FDG-PET. Previous studies have shown the diagnostic accuracy of APT imaging to be comparable with DSC-PWI, 13,16 and better than contrastenhanced T1-weighted imaging. 22 As in previous studies, our results also demonstrated excellent interrater reproducibility in the measurement of APT.…”
Section: Additive Value Of Apt Imaging To Dwi For Glioma Gradingmentioning
confidence: 96%
See 3 more Smart Citations
“…This study confirmed that APT imaging can be used for grading glial tumors, with a diagnostic accuracy comparable with that of other imaging biomarkers derived from DWI and FDG-PET. Previous studies have shown the diagnostic accuracy of APT imaging to be comparable with DSC-PWI, 13,16 and better than contrastenhanced T1-weighted imaging. 22 As in previous studies, our results also demonstrated excellent interrater reproducibility in the measurement of APT.…”
Section: Additive Value Of Apt Imaging To Dwi For Glioma Gradingmentioning
confidence: 96%
“…3,[11][12][13][14][15][16][17][18] However, details of the relationships between APT imaging and other clinical imaging parameters of malignancy have yet to be fully elucidated. This study confirmed that APT imaging can be used for grading glial tumors, with a diagnostic accuracy comparable with that of other imaging biomarkers derived from DWI and FDG-PET.…”
Section: Additive Value Of Apt Imaging To Dwi For Glioma Gradingmentioning
confidence: 99%
See 2 more Smart Citations
“…Relatively higher APT signals generally indicate elevated exchange rates resulting from increased protein concentration [16, 17]. Although the clinical applications of APT imaging remain in their investigative stages, this modality has demonstrated promise for the evaluation of brain development [18] and the characterization and grading of brain tumors [1923]. …”
Section: Introductionmentioning
confidence: 99%